NCI’s Work to Advance Cancer Research while Responding to the COVID-19 Pandemic - Singer, Dinah S. (Cancer Cell, 2020)
During the COVID-19 pandemic, the National Cancer Institute (NCI) is bringing to bear its considerable expertise and capabilities to understand, treat, and prevent the disease. While responding to the pandemic, NCI’s priority remains the advancement of cancer research. NCI has implemented many flexibilities for grantees and trainees.